Mamíferos marinos varados en la costa sur-central del Perú durante El Niño 1997-9 - Apaza, Manuel (2025)
During the 1997-98 El Niño event, an assessment of marine mammal strandings was conducted from August 1997 to April 1998 between 15°22' and 15°27' S. This assessment encompassed 30.4 km of coastline, distributed in seven sectors located along the borders of the Ica and Arequipa departments, during which 7 marine mammal species and 2500 stranded specimens were recorded in the study area. Otaria byronia (67.88%) and Arctocephalus australis (31.48%) accounted for 99.36% of the total strandings. The remaining five marine mammal species included Physeter macrocephalus, Phocoena spinipinnis, Lagenorhynchus obscurus, Tursiops truncatus, and Lontra felina, only accounted for 0.64% of specimens. Both Otariidae species exhibited similar stranding patterns, and a statistical correlation was found with sea surface temperature (SST). Otaria byronia showed increased mortality in February 1998, while Arctocephalus australis peak mortality occurred in January 1998, aligning with the reproductive seasons of both species. The Guanera-La Lobera sector recorded the highest number of strandings, attributed to its proximity to the Punta San Juan National Reserve, which shelters large colonies of both species. Analysis of the stranded specimens in the Otariidae indicated a strong correlation in age group differentiation, resulting in high mortality among females and juveniles, who accounted for 80.3% of O. byronia and 63.5% of A. australis. Overall, these findings underscore the vulnerability of marine mammals to environmental changes caused by El Niño events.